ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI KAIN TENUN BIMA DI MUTMAINAH KOTA BIMA - Iyelda, Nafisa; Syaframis, Nur Fetiningsih; Ariyanto, Yogi (Universitas Islam Syekh-Yusuf, 2021)
This study aims to determine the analysis of the effect of price and product quality on buying interest in Bima woven fabrics in Mutmainah Kota. The population used in this study were consumers at Mutmainah Kota Bima, with a total of 50 respondents. The method used in this study is multiple linear regression analysis. With the help of Microsoft Excel and the SPSS 23 software. The independent variables of this study are price (X1) and product quality (X2). The variable attached to this research is buying interest (Y). The results of this study indicate that the price, promotion and quality of the product. simultaneous influence on buying interest.